2020
DOI: 10.2147/imcrj.s275693
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diagnosis and Treatment of Paroxysmal Sympathetic Hyperactivity in Medical ICU, University of Gondar Hospital, Northwest Ethiopia: A Case Report</p>

Abstract: Background Paroxysmal sympathetic hyperactivity (PSH) is a neurologic syndrome characterized by paroxysmal and simultaneous occurrence of hypertension, hyperpyrexia, tachycardia, tachypnea, diaphoresis and dystonic posturing due to surge in sympathetic outflow after acquired brain injuries. Diagnosis of PSH is made using the paroxysmal sympathetic hyperactivity-assessment measure (PSH-AM) score, which comprises “clinical features severity” (CFS) score and “diagnosis likelihood tool” (DLT) score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…PSH is only a reflection of disease severity and does not affect prognosis. The findings of the literature review revealed that most studies reported improvement in patients discharged from the hospital, and only a few studies reported death or complications [ 40 ]. However, few patients had a discharge follow-up GCS or disability scale score to specifically assess prognosis.…”
Section: Prognosis Of Pshmentioning
confidence: 99%
“…PSH is only a reflection of disease severity and does not affect prognosis. The findings of the literature review revealed that most studies reported improvement in patients discharged from the hospital, and only a few studies reported death or complications [ 40 ]. However, few patients had a discharge follow-up GCS or disability scale score to specifically assess prognosis.…”
Section: Prognosis Of Pshmentioning
confidence: 99%